Applied solid state science. advances in materials and device research - Wolfe, Raymond; Kahng, Dawon (Applied solid state science. Supplement, 1985)
Silicon Integrated Circuits, Part 2 covers some of the most promising approaches along with the new understanding of processing-related areas of physics and chemistry. The first chapter is about the transient thermal processing of silicon, including annealing with directed-energy beams and rapid isothermal annealing; adiabatic annealing with laser and electron beams; pulsed melting; thermal flux annealing; rapid isothermal annealing; and several applications stemming from rapid annealing and semiconductor processing with directed-energy beams. The second chapter is concerned with the use of el.